2010
DOI: 10.1111/j.1600-0838.2009.00963.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an anterior cruciate ligament injury prevention program on performance in adolescent female soccer players

Abstract: Female soccer players are three times more likely to suffer a non-contact anterior cruciate ligament (ACL) tear compared with male soccer players. Several ACL injury prevention programs have been developed and are used to reduce injury risk. However, to date there is limited information on how such programs affect physical performance. The aim of this randomized controlled study was to investigate the effects of the Prevent Injury Enhance Performance (PEP) program in adolescent female soccer players. Four socc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
85
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(95 citation statements)
references
References 51 publications
5
85
5
Order By: Relevance
“…Our results are in agreement with two previous studies in girls' football that both failed to show any performance improvements from "the 11" [17], and the PEP [19]. In contrast, two other studies showed positive effects on performance from similar neuromuscular training programmes [2,12].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results are in agreement with two previous studies in girls' football that both failed to show any performance improvements from "the 11" [17], and the PEP [19]. In contrast, two other studies showed positive effects on performance from similar neuromuscular training programmes [2,12].…”
Section: Discussionsupporting
confidence: 93%
“…Still, we found no improvements in SEBT from our intervention, unlike another study where significant improvements in the posterolateral and posteromedial directions were seen in youth female football players after an 8-week neuromuscular training programme [3]. Plyometric exercises were included in other similar neuromuscular programmes [2,9,12,17,19] but not in ours, and it is more likely that an improvement in jumping or sprinting performance would have been achieved if a plyometric training component was included. However, there is no clear trend in the literature about the effect of adding plyometrics, where two of the previous studies showed improvements in jumping ability [2,12], and two reported no effects [17,19].…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations